Diagnostic Accuracy of Fine Needle Aspiration Cytology in Salivary Gland Lesions: A Teaching Hospital Based Study - Priyanka Singh; Shubhranshu Shekhar (Asian Journal of Medical Research, 2018)
Background: Fine needle aspiration cytology (FNAC) salivary gland (SG) is accurate, simple, rapid, inexpensive, well tolerated and harmless for the patient. Fine needle aspiration (FNA) cytology of the SG is an accepted, sensitive and specific technique in the diagnosis of both neoplastic and non-neoplastic lesions. Subjects and Methods: This retrospective study was conducted in the pathology department and (56) fifty six cases of salivary gland lesions, attending the outpatient and inpatient wards of surgery and ENT department of a tertiary care hospital were included in the study. The cases were thoroughly interrogated, clinically examined and relevant investigations done. FNAC procedure was explained to the patient and patient was placed in a comfortable position. Results: Maximum number of cases was observed in age group 25-34 years and there were 34(60.7%) male and 22(39.3%) female cases in this study. Commonest gland involved was parotid (71.4%, 40/56), followed by submandibular gland (25.0%, 14/56) and minor salivary glands (1.7%, 1/56) whereas no case of sublingual salivary gland lesion was observed in the present study. Conclusion: FNAC of the salivary gland is a safe and reliable technique in the primary diagnosis of salivary gland lesions. Although, limitations are encountered while predicting specific lesions on cytology, especially when dealing with cystic and some malignant lesions.